Perlindungan Hukum Jasa Pengangkut Barang (PORTER) Dalam Pendakian Di Taman Nasional Gunung Rinjani - Rezah Pahlevi; H. Zaeni Asyhadie (Fakultas Hukum Universitas Mataram, 2022)
This research aims to study the legal protection against the portersin climbing National Park of Rinjani Mountain as well as the factors that affect such legal protection.This study is an empirical legal research that uses facts taken from human behavior.This research shows that: there are still many portersdo not have a licence as a porter from the Office of National Park of Rinjani Mountain which results in lack of legal protection which can be provided by trekking organizers, whereas working as a porter is a high-risk job for the reason that the terrain traversed is very steep, namely the mountain.